1998
DOI: 10.1111/j.1439-0442.1998.tb00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Field Isolates of Mycoplasma ovipneumoniae Exhibit Distinct Cytopathic Effects in Ovine Tracheal Organ Cultures

Abstract: Ovine tracheal ring explants were infected with four different Mjcophsma ovipneumonzae and one M. utginini field isolate and their ability to induce cytopathic effects was tested by measuring ciliary activity and intracellular calmodulin release. Infected tracheal rings showed significantly decreased ciliary activity as compared to the non-infected control rings. There were, however, marked differences between isolates in the onset and severity of the effects which correlated with their ability to produce hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
(28 reference statements)
0
24
0
Order By: Relevance
“…It is possible that during the lag period, M. ovipneumoniae colonized the upper respiratory tract of at least two bighorn sheep and predisposed them to the tagged M. haemolytica, but whether M. ovipneumoniae played any role in the other two bighorn sheep seems even less certain, based on available data (Table 2). In domestic sheep, M. ovipneumoniae has been shown to render the cilia on the epithelial cells of the upper respiratory tract dysfunctional (Jones et al, 1985;Niang et al, 1998). Previous studies have shown that M. ovipneumoniae does not kill bighorn sheep (Besser et al, 2008) but can predispose them to M. haemolytica infection (Dassanayake et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that during the lag period, M. ovipneumoniae colonized the upper respiratory tract of at least two bighorn sheep and predisposed them to the tagged M. haemolytica, but whether M. ovipneumoniae played any role in the other two bighorn sheep seems even less certain, based on available data (Table 2). In domestic sheep, M. ovipneumoniae has been shown to render the cilia on the epithelial cells of the upper respiratory tract dysfunctional (Jones et al, 1985;Niang et al, 1998). Previous studies have shown that M. ovipneumoniae does not kill bighorn sheep (Besser et al, 2008) but can predispose them to M. haemolytica infection (Dassanayake et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These latter consequently produced less H 2 O 2 in the presence of glycerol compared to the highly virulent African strains. It has been proposed that H 2 O 2 production of certain pathogenic Mycoplasma species causes lysis of erythrocytes, peroxidation of lipids of infected fibroblasts, and inhibition of ciliary movement in infected tracheal organs (34,45). Using catalasedeficient mice, H 2 O 2 production of Mycoplasma pulmonis was suggested as a mycoplasmal virulence factor (15 …”
mentioning
confidence: 99%
“…Mycoplasma ovipneumoniae (M. ovipneumoniae, MO) has been identified as a pathogenic agent of chronic nonprogressive infection of pneumonia in sheep and goats [14]; the nature between a protective and a pathological host response of MO infection currently remains largely unknown. In this regard, the role of capsular polysaccharide (CPS), a major active component for cellular adherence, invasion, immune modulation, and virulence of M. ovipneumoniae remains undefined [5], although several lines of evidences have shown that M. ovipneumoniae is able to produce polysaccharide capsules for facilitating its adherence to ciliated epithelium [3, 6].…”
Section: Introductionmentioning
confidence: 99%